Respostas

2013-12-10T00:33:56-02:00
F(0)= 0.2 - 2.0 - 3 = 0 - 2-3 = -1
Simplesmente errada. f(x) = 0 , sendo que f(x) = y.
2013-12-10T01:07:48-02:00
X² - 2x - 3 = 0
a = 1            b = - 2               c = - 3
∆ = b² - 4 . a . c 
∆ = (- 2)² - 4 . 1 (- 3)
∆ = 4 + 12
∆ = 16
x =   - b + √∆
      ----------------
            2a
x = - (- 2) 
+ √16
      --------------------
            2 . 1
x = 2 + 4
     --------
        2
x' = 2 + 4 
         2
x' = 6 ÷ 2
x' = 3

x" = 2 - 4 
         2
x" = - 2 
÷ 2
x" = - 1
Resposta: {3; - 1}
1 4 1